1992
DOI: 10.1093/nar/20.15.4061
|View full text |Cite
|
Sign up to set email alerts
|

Hairpin and parallel quartet structures for telomeric sequences

Abstract: The role of thymine residues in the formation of G-quartet structures for telomeric sequences has been investigated using model oligonucleotides of the type d(G4TnG4), with n = 1-4. Sequences d(G4T3G4) and d(G4T4G4) adopt a G-quartet structure formed by hairpin dimerization in 70 mM NaCl as judged by a characteristic circular dichroism signature with a 295 nm positive and 265 nm negative bands while d(G4TG4) adopts a parallel G-quartet structure like d(G12) which exhibits a strong positive band at 260 nm and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
341
4
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(393 citation statements)
references
References 40 publications
45
341
4
3
Order By: Relevance
“…UV-melting experiments show that all sequences exhibit an invert transition at 295 nm (as shown in Supporting Information), which is a typical characterization of G-quadruplex denaturation [50], inferring that all DNA samples were folded into specific G-quadruplex motifs. Furthermore, the CD spectra of all sequences present a positive CD signal around 265 nm and a negative one at 240 nm (as shown in Supporting Information), which are typical parallel-stranded G-quadruplex features [51]. It is confirmed that all DNA samples with same core sequence folded into similar expected parallel-stranded G-quadruplex motifs.…”
Section: Verification Of the Secondary Structures Of All C-myc G-quadsupporting
confidence: 54%
“…UV-melting experiments show that all sequences exhibit an invert transition at 295 nm (as shown in Supporting Information), which is a typical characterization of G-quadruplex denaturation [50], inferring that all DNA samples were folded into specific G-quadruplex motifs. Furthermore, the CD spectra of all sequences present a positive CD signal around 265 nm and a negative one at 240 nm (as shown in Supporting Information), which are typical parallel-stranded G-quadruplex features [51]. It is confirmed that all DNA samples with same core sequence folded into similar expected parallel-stranded G-quadruplex motifs.…”
Section: Verification Of the Secondary Structures Of All C-myc G-quadsupporting
confidence: 54%
“…As the percentage of PEG increases to 20%, the shoulder at 292 nm gradually fades away and the peak at 272 nm intensifies. These spectra have characteristics similar to a fully parallel stranded structure [45]. Further, these spectra are strikingly similar to those reported by us for DNA oligomers of sequence (CCCCTTTTGGGGT 1-4 GGGG ) which self-assemble into high molecular weight species of multiple molecularties in the presence of Mg 2+ [46,47].…”
Section: Introductionsupporting
confidence: 86%
“…It is known that a parallel G-quadruplex gives a positive CD peak at 260 nm, while an antiparallel G-quadruplex gives a positive CD peak at 295 nm either with or without a positive CD peak at 260 nm in the presence of monovalent cations. 27,28 A peak was observed at 260 nm of CD and the peak intensity increased as the concentration of K + ions increased, with maximum peak intensity at 10 mM KCl (Fig. 3A).…”
Section: Introductionmentioning
confidence: 95%